Description of Orthopaedic Trauma and Non-Trauma Cases in Emergency Unit of RSUD H. Boejasin 2017–2022 - Pratama, Yudha; Iqbal, Muhammad; ‘Addawani, Musyaffa (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Orthopedic cases are still considered as the biggest cause of mortality and morbidity in developing countries. An understanding of epidemiology, expected to help related parties to plan better management. The aim of this study was to determine the prevalence and characteristics of trauma and non-traumatic cases in orthopedics. This research is a retrospective descriptive study. Data collection was carried out retrospectively from the medical records of orthopedic patients admitted to Emergency Department of H. Boejasin Hospital from 2017-2022. There were 137 samples that met the inclusion criteria. A total of 128 patients (93.43%) were categorized as trauma and 9 patients (6.56%) were non-trauma. Orthopedic patients are dominated by males with age in the range of 18-60 years, namely 84 patients (61.32%). 77 patients (56.20%) used BPJS as financing. Trauma is the most frequent cause of patients being brought to the emergency department, which is dominated by men of reproductive age. Health insurance plays an important role in helping patients pay for treatment.